Uso de desechos de yuca (Manihot esculenta Crantz) en la remoción de verde y naranja de metilo - Becerra-Quintana, Rubén; Lozada, María; Quintana-Mendoza, José; Torres, Alexandra; Henao, José (Revista Científica, 2023)
Using cassava roots waste (Manihot esculenta Crantz), a biochar-type material was synthesized for removal of dyes. Work was carried out with cassava flour summited to 673 K and 80 mbar. The material was characterized by Thermogravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), Attenuated total reflection infrared spectroscopy (ATR-FTIR), Scanning electron microscopy (SEM) and X-ray powder diffraction analysis (PDRX). These analyses showed that the obtained material was thermally stable with sphere aggregates (10 µm diameter), amorphous structure of lignocellulose and type A starch crystalline structure. Synthesized biochar adsorbed methyl orange (116,4 ± 0,2 mg/g and methyl green (94,2 ± 0,2 mg/g) at 308 K. the foregoing demonstrates the ability of this material to remedy contaminated water.